Phytochemistry of Calophyllum andersonii and Calophyllum wallichianum and their antibacterial activities - Tee, Keng Hong (2018)
Plants from the genus Calophyllum are known for their rich content of secondary metabolites, especially phenolic compounds such as coumarins, xanthones and flavonoids. Many of these compounds are identified to be the main contributors of the medicinal properties of the plants. Even today, human are still heavily relying on the natural resources to develop new drugs and medicines. The threats of existing and emerging diseases are to be managed by discovering new lead compounds. Natural product research is one of the various approaches to this. This research project aimed to isolate antibacterial compounds which can lead to the discovery of new antibacterial drug candidates for future drug discovery research. Phytochemical studies have been carried out on the stem bark of two selected plant species, Calophyllum andersonii and Calophyllum wallichianum. A total of five xanthones and one terpene were isolated from the hexane and chloroform extracts of Calophyllum andersonii. The terpene is friedelin (79) while the xanthones are macluraxanthone (74), pyranajacareubin (75), calaxanthone I (76), caloxanthone C (77), and euxanthone (78). All of the compounds were isolated for the first time from the plant. Meanwhile, two coumarins and two terpenes were afforded from the hexane and chloroform extracts of Calophyllum wallichianum. The terpenes are friedelin (79) and stigmasterol (82) while the coumarins are wallimarin T (80) and calanolide E (81). Wallimarin T (80) is a new coumarin. The structures of the isolated compounds were identified using spectroscopic methods such as MS, IR and NMR. The plant extracts and two isolated compounds were examined for their antibacterial activities. The samples were tested against four bacterial strains, namely Bacillus cereus, B. megaterium, B. pumilus and B. subtilis. The tests conducted include disc diffusion test, minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) assay. In the disc diffusion test, wallimarin T (80), calanolide E (81), the hexane and chloroform extracts of both plants were tested. All of the samples showed activities against the bacteria, expect wallimarin T (80). The samples that showed activities were then further tested for their MIC values. The plant extracts showed moderate inhibition against all four bacteria, with MIC values ranging from 0.156 to 1.25 mg/ml. The chloroform extract of Calophyllum andersonii showed significant inhibition on B. pumilus (MIC = 0.039 mg/ml) while calanolide E (81) showed weak inhibition on all the bacteria with MIC value ranging from 0.25 to 0.5 mg/ml. The extracts of Calophyllum wallichianum showed high bactericidal concentrations ranging from 2.5 to 10 mg/ml. Extracts of Calophyllum andersonii recorded lower MBC value compared to extracts of Calophyllum wallichianum, ranging from 0.039 to 1.25 mg/ml. Meanwhile, calanolide E (81) did not show any bactericidal activity.